The intersection between politics, ethnicity, crime and violence in Guyana - Ifill, Melissa (The Palgrave handbook of Caribbean criminology, 2024)
Violence, crime and insecurity have challenged democratic governance in Guyana. Violence and crime equally impede human development since they generate fear and anxiety, and in effect deny an essential form of freedom, that is, freedom from fear. Critical to understanding crime and violence in Guyana is an analysis of their political and ethnic manifestations. The variables crime, violence, ethnicity and politics have intersected and intertwined and at times they appear indistinguishable, particularly during elections. This chapter explores the connections between crime, violence, politics and ethnicity. It reviews the historic and contemporary linkages between ethnicity, politics, crime and violence. It then examines ethnic contestation and conflict, particularly during elections and the types of violence used to serve political and ethnic agendas.